Habit formation in an interdependent world economy - Shinsuke Ikeda; Ichiro Gombi (Osaka University, Institute of Social and Economic Research (ISER), 2004)
Economic interdependence of heterogeneous habit forming consumers is examined by using a two-country model. Due to endogenous interest rate adjustments, consumption-habit dynamics in one country are affected by the other country's habits and preferences. To characterize the interactive dynamics, we construct an aggregate world felicity function from individual countries' felicity functions and introduce a global aggregate habit capital, defined as the sum of individual countries' habit capitals. External indebtedness depends crucially on international differences in habit-adjusted disposable income less habitual living standard. The international average of, and difference in, the strength of habit formation play a key role in macroeconomic adjustment and the effects of fiscal policies. An increase in fiscal spending in one country can make that country better off, and the neighbor worse off, due to intertemporal terms-of-trade effects.
Keywords: F41; D90; 330; habit formation; two-country model; fiscal policy; Konsumentenverhalten; Nachfrageinterdependenz; Internationale Staatsschulden; Öffentliche Ausgaben; Terms of Trade; Zwei-Länder-Modell; Theorie